Language change and linguistic theory - Miller, D. Gary (Oxford University Press, 2011)
This book investigates a large range of changes and their motivations in all parts of the grammar and lexicon. The core argument is that, in the absence of a Grand Unification Theory in linguistics, a unified account of change is impossible without ignoring the bulk of natural language changes